The Syndrome of No One Knows What the Patient Has - Alfredo Darío Espinosa Brito (Medisur)
This paper presents a series of considerations on the syndrome known as no one knows what the patient has, a phrase ingeniously coined at the University General Hospital of Cienfuegos to refer to those patients whose underlying condition cannot be clearly established despite countless efforts of all sorts: application of clinical methods, investigations, continuous diagnostic discussions, and consultations with the most diverse specialists. This represents a stressful situation for patients, relatives, and medical staff, with a significant impact not only on the health care setting, but also on administrative, social, ethical, and possibly legal spheres.